Securing the state, undermining democracy: internationalization and privatization of western militaries - Nicole Deitelhoff; Anna Geis (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2009)
Changes in the field of security since the 1990s triggered off a number of still continuing military transformations in liberal democracies. Since their armed forces were designed for the purposes of the bipolar Cold war security constellation, they have been “redesigned” according to the new tasks as agreed upon in the new NATO strategic concepts or the assignments for the Europeanized forces within the European Union: Conflict prevention, crisis intervention, counter-terrorism have been added to the range of deployment missions. This recent transformation of the armed forces is pushed ahead in the political spirit of new public management well known from other policy areas in the OECD countries. The proclaimed reforms are guided by efficiency and effectiveness principles only, issues of democratic control and integration of the armed forces into the society are marginalized in the political discourse. But integration and cooperation within international organizations is only one of the two trends detrimental to democratic control of the military; increasing contracting with Private Security and Military Companies is the other. Contracting is intended to reduce political and financial costs and risks for Western governments. The authors argue that, in the long run, both trends of privatization and internationalization, though they seem to run into opposite directions from a purely etatist perspective, result in the joint effect of exacerbating democratic control and accountability of security policies. This point is illustrated by the employment of private military companies by the US government agencies and US military and the reform of the German armed forces. – – Seit Ende des Ost-West-Konflikts befinden sich die westlichen Streitkräfte in einem anhaltenden Transformationsprozess. Waren die Streitkräfte zuvor an der bipolaren Sicherheitskonstellation des Kalten Krieges ausgerichtet, werden sie seit 1990 umstrukturiert, um neue Missionen zu erfüllen, wie sie in den strategischen Konzepten der NATO oder den Aufgabenfeldern der Europäischen Sicherheits- und Verteidigungspolitik definiert sind. Unter den Vorzeichen eines New Public Managements vorangetrieben, das in den letzten Jahrzehnten als ökonomisch inspiriertes Reformprinzip bereits zahlreiche andere Politikfelder der OECD-Staaten geprägt hat, sind die Umstrukturierungen der Streitkräfte vorwiegend an Effizienz- und Effektivitäts-Gesichtspunkten orientiert. Fragen der demokratischen Kontrolle und der Integration des Militärs in die jeweilige Gesellschaft werden dagegen im politischen Diskurs vernachlässigt. Zwei Entwicklungstrends kennzeichnen derzeit die westliche Sicherheits- und Verteidigungspolitik: die Integration und Kooperation westlicher Streitkräfte im Rahmen von internationalen Organisationen sowie der zunehmende Einsatz privater Sicherheitsunternehmen. Obwohl Internationalisierung und Privatisierung von Sicherheitspolitik in einer staatszentrierten Perspektive auf den ersten Blick gegenläufige Tendenzen einer Stärkung der Exekutive einerseits und der Schwächung des Staates andererseits zu markieren scheinen, tragen jedoch beide zu einer Schädigung der nationalstaatlichen Demokratie bei. Diese These erläutern die Autorinnen anhand des vermehrten Rückgriffs der US-amerikanischen Regierung auf private Sicherheitsanbieter sowie der Transformation der deutschen Streitkräfte.
Keywords: 350; Militär; Reorganisation; New Public Management; Privatisierung; Sicherheitsgewerbe; Sicherheitspolitik; Demokratie; Kritik; USA; Deutschland